Genetic manipulation of microalgae for enhanced biotechnological applications - Pandey A.; Kant G.; Afzal S.; Singh M.P.; Singh N.K.; Kumar S.; Srivastava S. (My University, 2025)
Microalgae are considered a superior feedstock compared to the terrestrial plants. Their biomass is loaded with lipids, carbohydrates, and other valuable compounds. Due to the high cultivation cost and several technological limitations, microalgae are not economically viable. Genetic manipulations provide a range of methods for manipulating desired genes/pathways to increase the desirable compounds’ output. In the current scenario, the genetic engineering of microalgae could be achieved by various methods such as gene mutation, gene silencing, targeted gene delivery, and emerging tools such as CRISPR-Cas9, transcription activator-like effector nuclease, etc. This chapter reviews the significant advantages of conventional as well as promising genome-editing tools in the field of microalgal research, which may be extended to industrially relevant organisms. Further, the potential of genome editing was evaluated to modify the microalgae for enhanced production of lipid-derived biofuels, starch-derived alcohol, and other valuable products. © 2022 Elsevier Inc. All rights reserved.